Movements in Ethiopia, Ethiopia in Movement. Volume 1 Proceedings of the 18th International Conference of Ethiopian Studies (Corne de l'Afrique contemporaine / Contemporary Horn of Africa, 2016)
In November 2012, the 18th International Conference of Ethiopian Studies was convened in Dire Dawa, a cosmopolitan city in the eastern lowlands of Ethiopia. This event gathered more than 300 international scholars from all disciplines of the humanities and social social sciences. Under the general theme of 'movement' these two volumes gather a collection of 70 papers that reflect recent trends in the field of Ethiopian studies. From local studies to regional and international perspectives, these studies question long term historical processes and current social and economic transformations. A number of contributions explore and give access to fresh sources of knowledge from unpublished or rediscovered texts and documents, from recordings of oral information, or from ethnographic observation. They also review literature, challenge conventional ideas and propose critical investigations on past and present issues, such as interethnic relations, women's role, development policies and their impact.